2013
DOI: 10.1111/inr.12038
|View full text |Cite
|
Sign up to set email alerts
|

Motives for self‐harm: views of nurses in a secure unit

Abstract: Improved understanding of self-harm and its motives may result in improved nurse-user relationships and thus safer and more effective care provision.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(43 citation statements)
references
References 18 publications
1
42
0
Order By: Relevance
“…The internalisation of anti-LGBTI attitudes, in other words, internalised homonegativity can have a devastating effect on the mental well-being of individuals. It is perceived as a significant correlate of substance use and misuse and suicide attempts and successful suicides (Sandy 2013), a view that is also reflected in this study. In addition to this association, the relationships between other mental health problems and human rights violations of LGBTI students are illustrated in Figure 1, entitled rights-impact conceptual model (RIM).…”
Section: Violation Of Human Rightssupporting
confidence: 61%
See 1 more Smart Citation
“…The internalisation of anti-LGBTI attitudes, in other words, internalised homonegativity can have a devastating effect on the mental well-being of individuals. It is perceived as a significant correlate of substance use and misuse and suicide attempts and successful suicides (Sandy 2013), a view that is also reflected in this study. In addition to this association, the relationships between other mental health problems and human rights violations of LGBTI students are illustrated in Figure 1, entitled rights-impact conceptual model (RIM).…”
Section: Violation Of Human Rightssupporting
confidence: 61%
“…In this study, participants reported that lesbian or transgender students dated males, and restricted their socialisation to only a few friends to avoid identification of their sexual orientation. Concealment of any kind, especially in the context of sexuality, may have a paradoxical effect of leading to feelings of guilt, inferiority, anxiety and hopelessness (Sandy 2013). This is because of the constant preoccupation with hiding.…”
Section: Discussionmentioning
confidence: 99%
“…Self-harm is a significant international public health problem with increasing incidence (Sandy, 2013). In a document published by the World Health Organisation (WHO, 2009), it is indicated that globally between 10 and 100 million incidents of self-harming behaviour occur every year.…”
Section: Introductionmentioning
confidence: 99%
“…Tension release is one of the most commonly cited reasons by users, as they tend to report emotional release and subsequent feelings of calm following acts of self-harm (Sandy, 2013). Communication of unbearable feelings (such as anger), self-cleansing, driving others away, regaining control of their lives and coping with stigmatisation and labelling are motives also frequently expressed by users (Bosman & van Meijel, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation